Anterior cruciate ligament injuries in the National Hockey League: Epidemiology and performance impact - Longstaffe, R.; Leiter, J.; MacDonald, P. (Clinical Journal of Sport Medicine, 2020)
Objective: To determine the incidence of anterior cruciate ligament (ACL) injuries in the National Hockey League (NHL) and to examine the effects of this injury on return-to-play status and performance. Design: Case series; level of evidence, 4. Methods: This was a 2-phase study. Phase I used the NHL electronic injury surveillance system and Athlete Health Management System to collect data on ACL injuries and man games lost over 10 seasons (2006/2007-2015/2016). Data collected in phase I were received in deidentified form. Phase II examined the performance impact of an ACL injury. Players were identified through publically available sources, and performance-related statistics were analyzed. Data collected in phase II were not linked to data collected in phase I. A paired t test was used to determine any difference in the matching variables between controls and cases in the preinjury time period. A General linear model (mixed) was used to determine the performance impact. Results: Phase I: 67 ACL injuries occurred over 10 seasons. The incidence for all players was 0.42/1000 player game hours (forward, 0.61; defenseman, 0.32, goalie, 0.08) and by game exposure was 0.2/1000 player game exposures (forward, 0.33; defenseman, 0.11; goalie, 0.07). Forwards had a greater incidence rate of ACL tears with both game hours and game exposures when compared with defensemen and goalies (P < 0.001, <0.001; P = 0.008, <0.001, respectively). Phase II: 70 ACL tears (60 players) were identified. Compared with controls, players who suffered an ACL tear demonstrated a decrease in goals/season (P < 0.04), goals/game (P < 0.015), points/season (0.007), and points/game (0.001). Number of games and seasons played after an ACL injury did not differ compared with controls (P = 0.068, 0.122, respectively). Conclusions: Anterior cruciate ligament injuries occur infrequently, as it relates to other hockey injuries. Despite a high return to play, the performance after an ACL injury demonstrated a decrease in points and goals per game and per season.